Trends in Kaposi's Sarcoma Morbidity: A Retrospective Cohort Study of Heart and Lung Transplant Recipients - Tal Serlin; Tuvia Ben Gal; Mordechai Kramer; Diana Sorin; Emmilia Hodak; Batya Davidovici (Medical Journals Sweden, 2021)
Data on post-transplant Kaposi's sarcoma in heart and lung transplant recipients are sparse. This study examined the incidence of biopsy-proven post-transplant Kaposi's sarcoma in thoracic organ recipients over a period of 20 years. As mammalian target of rapamycin inhibitors were introduced in 2006 as optional maintenance immunosuppressive therapy, the overall results were analysed and stratified into 2 groups: 1996 to 2005 and 2006 to 2016. A total of 867 transplant recipients met the study criteria. Post-transplant Kaposi's sarcoma was diagnosed in 7 (0.81%) patients. Five cases (0.19% of transplant recipients) were recorded in 1996 to 2005 and 2 (0.03% of transplant recipients) in 2006 to 2016 (p = 0.04). Multivariable logistic regression analyses identified the following as risk factors: period of transplantation (odds ratio (OR) 4.844, 95% confidence interval (95% CI) 1.156-20.291), age at transplantation (OR 1.066, 95% CI 0.992-1.145), and North African origin (OR 7.282, 95% CI 12.55-42.254). This study found a decreased incidence of post-transplant Kaposi's sarcoma over the last 20 years, mainly attributed